STRATEGI PENGAWASAN PANWASLIH KABUPATEN PIDIE PADA PEMILU TAHUN 2024 - Andri, Muhammad; Nelliyana, Nelliyana; Mulyadi, Mulyadi (Jurnal Sosial Humaniora Sigli, 2024)
This study identifies the supervision strategy of the Election Supervisory Committee (Panwaslih) of Pidie Regency in the 2024 election. The focus of this study includes the supervision strategy implemented, the effectiveness of the implementation of the supervision strategy, the evaluation process of the supervision strategy and the obstacles faced. The research method used is a qualitative approach with data collection through interviews, observations and document analysis. The results of the study indicate that the Pidie Regency Panwaslih has implemented several supervision strategies strategically and in a planned manner, thereby increasing the effectiveness of election supervision. The evaluation process was carried out by involving various parties to obtain constructive input. However, there are several obstacles in the implementation of the supervision strategy such as limited human resources (HR), lack of proactive community participation in participatory election supervision.  Keywords: Supervision Strategy, Election, Effectiveness, Evaluation, Obstacles